Heterogeneous distribution of fast and slow potassium channels in myelinated rat nerve fibres. - Röper, J (1989)
1. Potassium currents were measured in voltage-clamped single myelinated rat nerve fibres before and after paranodal demyelination with 0.2% pronase or 0.2% lysolecithin added to the external solution. Sodium currents were blocked by 300 nM-tetrodotoxin. For the purpose of comparison, intact frog nerve fibres were also investigated. 2. Our results suggest the existence of at least two distinct types of K+ channels in the intact node of Ranvier, one with slow and another with fast gating kinetics, in the ratio 4:1. 3. In the rat nodal membrane, slow K+ channels have voltage-dependent time constants of K+ deactivation with tau n = 68 ms at E = -105 mV and tau n = 26 ms at E = -150 mV at 20 degrees C. The activation curve of the slow K+ conductance is sigmoid with an inflexion point at -60 mV. This means that about 35% of the slow K+ channels are in the open state at the resting potential of -77 mV. Slow K+ channels could be blocked by 10 mM-tetraethylammonium chloride, but were insensitive to 4-aminopyridine. 4. After paranodal demyelination the ratio of fast to slow K+ channels increased from 17 to 83%. As in the frog (Dubois, 1981 alpha), the population of fast K+ channels in the rat may consist of two different subgroups, both of which can be blocked by 4-aminopyridine. 5. Demyelination was accompanied by an increase in the capacity current which was used to estimate the exposed membrane area. The density of slow and fast K+ channels was calculated from the quotient of the steady-state K+ conductance to membrane area. The density of the slow K+ channels is maximal in the nodal membrane and decreases to 1/31 in the internode. By contrast, the distribution of the fast K+ channels differs, their density being maximal in the paranode and decreasing to one-sixth in the node and internode.